Psychodiagnostics of Psychological Readiness of Candidates for Management of Correctional Facilities - Boris G Bovin; Ekaterina M Fedorova (Peoples' Friendship University of Russia (RUDN University), 2019)
The article presents the results of an empirical study conducted by the employees of the Research Institute of the Federal Penitentiary Service. The problems of the psychological selection of the employees enrolled in the reserve for the posts of heads of correctional institutions of the penitentiary system of the North Caucasus Federal District are considered. The sample consisted of 164 employees of corrective services, pre-trial detention centers, medical correctional institutions and correctional institutions in the territorial bodies of the Federal Penitentiary Service of Russia of the North Caucasus Federal District: age - from 25 to 45 years old, gender - male, work experience - from 3 to 10 years. The methods used in the centers of psychodiagnostics of the territorial bodies of the Federal Penitentiary Service of Russia were used in the psychological examination of candidates enlisted in the reserve for promotion, namely, MMPI and an expert survey. As a result of the study, the criteria for psychological readiness for managerial activities and psychological contraindications for holding a managerial position were determined. On the basis of a multiple regression analysis, a socio-psychological model, which determines the level of staﬀ readiness for management activities in correctional institutions of the Penal Enforcement System was also developed. The practical signiﬁcance of the study lies in the possibility of applying the developed model to the psychodiagnostic examination of candidates and the formation of a reserve for managerial positions.